Treatment of proteinuria with low-molecular-weight heparin after renal transplantation - Krzossok, Stefan; Birck, Rainer; Köppel, Hannes; Schnülle, Peter; Waldherr, Rüdiger; Woude, Fokko J. van der; Braun, Claude (Transplant international, 2004)
The development of nephrotic-range proteinuria after renal transplantation is an unfavourable prognostic factor for graft survival. In contrast to that in other nephropathies, the role of renin-angiotensin blockade in kidney transplantation is less well defined, and its anti-proteinuric effect is markedly reduced in the presence of segmental glomerulosclerosis. Here, we describe two patients who developed severe proteinuria after renal transplantation, despite effective blood pressure control with an ACE inhibitor. Histological changes were consistent with IgA-nephropathy and focal segmental glomerulosclerosis. Both patients were treated with low-molecular-weight heparin in addition to pre-existing ACE inhibition. This regimen led to a significant and long-lasting reduction of proteinuria. Our data suggest that low-molecular-weight heparin possesses strong renoprotective properties, thus confirming previous data from experimental nephropathies. This approach might represent a promising new strategy for treatment of proteinuria after kidney transplantation.
Gesehen am 31.05.2022